Penataan Pedagang Kaki Lima Sebagai Strategi Pengembangan Kesejahtraan Kota Manado - Kainage, Richard R; Kaunang, Markus ,; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2014)
Effort to organize street vendors conducted by the City of Manado rated yet able to provide maximum results in the effort to organize the city, increasing the infestation area and foster the creativity of the local economy. By him the necessary arrangement of vendors who carried through the arrangement of Human Resources, Organizational Structure and Design, and Culture or culture. This study concluded that the arrangement of street vendors in the city of Manado has not been done properly by the arrangement of resources and vendors implementing agency, the lack of proper structuring strategies of Manado City Government and has not been supported by good work culture.